If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(-1) + -8Y = 0 Multiply 7 * -1 -7 + -8Y = 0 Solving -7 + -8Y = 0 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -8Y = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -8Y = 0 + 7 -8Y = 0 + 7 Combine like terms: 0 + 7 = 7 -8Y = 7 Divide each side by '-8'. Y = -0.875 Simplifying Y = -0.875
| 7(1)-8Y=0 | | f(1)=7x^3-4x^2-28x+16 | | 2log(7x)+4=10 | | 5n=4n+6 | | 4+3r=16 | | 3x+1=12x+29 | | 6x-3=37-4x | | 3.14x4/3= | | -8+5c=6c | | 19-3j=7 | | 12x-8=62-2x | | z^2-7z= | | -2-4p=-7-5p | | -50.00+50x=300 | | (-9m+9)+(8m+8)= | | -q-5=4q | | -4-3m=19 | | (z-7)(z-7)= | | 5x-8=11+7x-2x | | (z-7)(z-7)=0 | | 2-27n=0 | | X+(x+2)+(x+4)=-15 | | 5x-8=11+7x-2 | | 0.75x+25=250.00 | | (X+1)(8x)=a | | 2(3x-3)=3(2x+2) | | 5y=-1x-3 | | r=2t+3 | | 8x=16+27 | | 2*(3x-8)+14=16 | | x*20/100=158 | | 2(3x-8)+14=16 |